2017
DOI: 10.1111/jbi.12934
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity and taxon pulse: the central influence of coastal geomorphology on genetic diversification and endemism of strict estuarine species

Abstract: Aim Sea‐level changes and coastal geomorphology (extension of continental shelves) have affected the pattern of diversification of brackish/freshwater fish populations due to the confluence of basins/estuaries during low sea‐level periods (opportunity) and isolation during high sea‐level periods. It is hypothesized that populations from estuaries in extensive continental shelves, which have greater potential for confluence, should have more opportunities for gene exchange than those in narrow continental shelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
2
18
1
Order By: Relevance
“…Global temperature increasing events are indicated during the Holocene (11.300 years until present) in tropical zones (Marcott et al, 2013), and their effects can cause significantly important oscillations in the demography and in the population genetics of many species including tiger sharks as observed herein. These signs of Ne oscillations over time have been demonstrated at several different species (Torres & Ribeiro, 2009;Von der Heyden et al, 2011;der Heyden et al, 2013;Teske et al, 2013;Lima et al, 2016;Baggio et al, 2017;Machado et al, 2017). Despite the occasional capability on reaching temperatures below 15°C, tiger sharks seem to prefer warmer waters.…”
Section: Genetic Diversity Demographic History and Conservation Stmentioning
confidence: 82%
“…Global temperature increasing events are indicated during the Holocene (11.300 years until present) in tropical zones (Marcott et al, 2013), and their effects can cause significantly important oscillations in the demography and in the population genetics of many species including tiger sharks as observed herein. These signs of Ne oscillations over time have been demonstrated at several different species (Torres & Ribeiro, 2009;Von der Heyden et al, 2011;der Heyden et al, 2013;Teske et al, 2013;Lima et al, 2016;Baggio et al, 2017;Machado et al, 2017). Despite the occasional capability on reaching temperatures below 15°C, tiger sharks seem to prefer warmer waters.…”
Section: Genetic Diversity Demographic History and Conservation Stmentioning
confidence: 82%
“…For example, using a paleodrainage reconstruction for the southeastern coast of Brazil, it was demonstrated that paleodrainages and its properties account for most of the genetic variation and diversity observed for the characid genus Hollandichthys based on mitochondrial DNA (Thomaz et al, 2015) and next generation sequencing data (Thomaz et al, 2017). Likewise, analyses that took into consideration fluctuations on sea level suggests its role in structuring genetic divergence and demographic history of other members of the coastal ichthyofauna (Baggio et al, 2017;Hirschmann et al, 2017;Lima et al, 2017;Ramos-Fregonezi et al, 2017;Tschá et al, 2016Tschá et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Here we provide reconstructions of paleodrainages using GIS technologies for the eastern coast of Brazil, and for a few basins in the northeast and south. Together they represent a significant expansion over the information to date, which is limited to a local analysis of paleodrainages (Dias et al, 2014;Thomaz et al, 2015; and of proposed paleo-connections among a set of specific Brazilian river basins (Baggio et al, 2017;Lima et al, 2017). We also characterize general properties of the inferred paleodrainages, including the geographic area spanned by each paleodrainage and the number of contemporary river basins associated with individual paleodrainages.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from a variety of sources [45][46][47][48][49][50][51] uphold abiotic factors as important drivers of evolution and speciation. This has led to proposed alternatives to the RQH which focus on the physical environment as the main driver of evolution.…”
Section: 'I'm Not Crazy My Reality Is Just Different Than Yours': Abmentioning
confidence: 99%